Large-Temporal-Numerical-Aperture Parametric Spectro-Temporal Analyzer Based on Silicon Waveguide - Haidong Zhou; Ningning Yang; Guoqing Liu; Liao Chen; Yi Wang; Chi Zhang; Kenneth K. Y. Wong; Xinliang Zhang (IEEE Photonics Journal, 2019)
The parametric spectro-temporal analyzer (PASTA) system has been demonstrated as a flexible tool in single-shot spectrum measurements, especially for ultrafast non repetitive phenomena with arbitrary waveforms. However, the highly nonlinear fiber (HNLF) based PASTA is subject to a limited spectral resolution across a limited observation bandwidth, because the inherent dispersion and dispersion slope of the HNLF restrict the temporal numerical aperture (NA) of the time lens of current PASTA systems. Therefore, in this work, we propose and experimentally demonstrate a PASTA based on a dispersion-engineered silicon waveguide with a much lower accumulated dispersion and slope to improve the temporal NA. Leveraging the short interaction length and dispersion-engineered waveguide, a broadband phase-matching condition can be obtained, and the limited converted pump bandwidth can be overcome by implementing the time lens on the silicon waveguide. Compared to the HNLF-based PASTA, the silicon waveguide improves the temporal NA by a factor of 2.5: a 2.5-nm bandwidth pump can theoretically achieve an ultrahigh optical resolution of 1.3 pm (limited to 20 pm because of the acquisition bandwidth limit) over a 21-nm observation bandwidth. Moreover, the silicon waveguide-based PASTA presents a new way to integrate the whole system because of the waveguide configuration, and is promising for real-time measurements, which has not been possible with most conventional optical spectrum analyzers.